Multicultural Disaster Mitigation Education in Elementary Schools: An Inclusive Approach to Disaster Risk Management - Lestari, Wiwik; Fatmawati , Laila (IAIN Madura, 2025)
Disaster mitigation education at the elementary school level plays a critical role in developing students’ awareness, preparedness, and collective responsibility toward disaster risks. In multicultural urban contexts such as Medan City, however, its implementation remains challenged by learning approaches that emphasize technical knowledge while overlooking socio-cultural diversity. This study explores the implementation of multicultural-based disaster mitigation education in elementary schools in Medan City and examines pedagogical practices and challenges encountered in diverse learning environments. Using a qualitative case study design, data were collected through in-depth interviews with 20 teachers, 50 students, and 10 parents, supported by classroom observations in five multicultural elementary schools. The findings reveal that integrating multicultural values into disaster mitigation education enhances students’ disaster risk awareness while fostering mutual respect, collaboration, and cross-cultural social solidarity. Contextual and inclusive pedagogical strategies enable students to understand disaster mitigation as a shared collective responsibility. Nevertheless, challenges persist, particularly regarding teacher preparedness, curriculum integration, and limited school–community collaboration. This study highlights the importance of culturally responsive curricula, sustained teacher capacity development, and strengthened partnerships among schools, families, and communities to improve the effectiveness of disaster mitigation education in multicultural settings.